2008
DOI: 10.1143/jjap.47.3196
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Poly(3-hexylthiophene)-Based Field-Effect Transistors with Silsesquioxane Gate Insulators

Abstract: The preparation of organic–inorganic hybrid gate dielectrics of poly(methyl silsesquioxane) (PMSQ) at a low processing temperature has been studied for use in organic field-effect transistors (OFETs) by the solution process. It is found that the electrical resistivity of a PMSQ film synthesized by a sol–gel method is significantly influenced by the synthesis conditions such as the type of organic solvent used and water content. PMSQ films prepared in toluene show a high resistivity of over 1014 Ω cm even at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…suggested that the leakage current could be attributed to the residual Si-OH groups in the PMSQ fi lms, resulting from incomplete cross-linking reactions. [ 22 , 23 ] In our previous studies, we systematically investigated the synthesis of PMSQ with the aim of reducing Si-OH concentration and obtained high insulating PMSQ fi lms with a low curing temperature of 150 ° C. [ 24 ] We also reported the surface energy control of our PMSQ dielectrics using silane-coupling SAMs with different organic end groups. [ 25 ] The fabrication of OFETs on plastic substrates using the PMSQ gate dielectrics has also been demonstrated.…”
Section: Doi: 101002/adma201001871mentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that the leakage current could be attributed to the residual Si-OH groups in the PMSQ fi lms, resulting from incomplete cross-linking reactions. [ 22 , 23 ] In our previous studies, we systematically investigated the synthesis of PMSQ with the aim of reducing Si-OH concentration and obtained high insulating PMSQ fi lms with a low curing temperature of 150 ° C. [ 24 ] We also reported the surface energy control of our PMSQ dielectrics using silane-coupling SAMs with different organic end groups. [ 25 ] The fabrication of OFETs on plastic substrates using the PMSQ gate dielectrics has also been demonstrated.…”
Section: Doi: 101002/adma201001871mentioning
confidence: 99%
“…Among the organic solvents of methanol, PGMEA, and toluene, the synthesis using toluene having lowest polarity leads to lowest SiOH concentration and highest electrical resistivity. [ 24 ] We have also optimized the synthesis condition using PGMEA, which is used as the diluted solvent of PMSQ solution, to simplify synthesis process and have found that PMSQ with low SiOH concentration can be obtained from the synthesis using PGMEA by increasing temperature from 50 ° C to 70 ° C for the polycondensation reaction. Thus, we used PMSQ solution synthesized using PGMEA in this study.…”
Section: Doi: 101002/adma201001871mentioning
confidence: 99%
“…The width of the Cr electrode was 50 μm. We used the crosslinking organic-inorganic hybrid polymer dielectric of poly (methylsilsesquioxane) (PMSQ) [9], [16], which was prepared in our laboratory, as a polymer gate insulator. The PMSQ layer was fabricated onto the substrate by spin coating, followed by curing at 150 • C for 1 h in ambient air.…”
Section: Methodsmentioning
confidence: 99%
“…We also see that the capacitance remains unchanged for frequency sweep from 1 Hz to 100 kHz. This is attributed to an extremely low density of ionic impurities of our PMSQ gate insulators [9], [16]. Figure 5 shows the output (drain current I D -drain voltage V D ) and transfer (I D -V G ) characteristics of PBTTT FET with self-aligned electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the poly(methyl silsesquioxane) (PMSQ) has emerged recently as the most attractive organic-inorganic hybrid dielectrics. It was suggested that the high off current was caused by residual silanol groups due to incomplete polycondensation of PMSQ 21 . Finally, PMSQ is chemically resistant to common organic solvents (such as methylbenzene, alcohol, chloroform, etc), making it stable during solution deposition of organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%